2016
DOI: 10.1177/1535370216658144
|View full text |Cite
|
Sign up to set email alerts
|

Liver metastases: Microenvironments andex-vivomodels

Abstract: The liver is a highly metastasis-permissive organ, tumor seeding of which usually portends mortality. Its unique and diverse architectural and cellular composition enable the liver to undertake numerous specialized functions, however, this distinctive biology, notably its hemodynamic features and unique microenvironment, renders the liver intrinsically hospitable to disseminated tumor cells. The particular focus for this perspective is the bidirectional interactions between the disseminated tumor cells and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 126 publications
(262 reference statements)
3
104
0
1
Order By: Relevance
“…"We recently showed that the simultaneous targeting of glucose and glutamine under calorie restriction could signi icantly reduce systemic metastatic cancer in the VM-M2 mouse model" [17]. "The liver is a highly metastasis-permissive organ" [20]. "This distinctive biology, notably its hemodynamic features and unique microenvironment, renders the liver intrinsically hospitable to disseminated tumor cells" [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…"We recently showed that the simultaneous targeting of glucose and glutamine under calorie restriction could signi icantly reduce systemic metastatic cancer in the VM-M2 mouse model" [17]. "The liver is a highly metastasis-permissive organ" [20]. "This distinctive biology, notably its hemodynamic features and unique microenvironment, renders the liver intrinsically hospitable to disseminated tumor cells" [20].…”
Section: Discussionmentioning
confidence: 99%
“…"The liver is a highly metastasis-permissive organ" [20]. "This distinctive biology, notably its hemodynamic features and unique microenvironment, renders the liver intrinsically hospitable to disseminated tumor cells" [20]. "Cancer metastasis is a highly complex process that involves aberrations in gene expression by cancer cells leading to transformation, growth, angiogenesis, invasion, and dissemination, survival in the circulation, and subsequent attachment and growth in the organ of metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very interesting approach to model the complex sinusoid-like structures using 3D perfused hepatic co-cultures in a microfluidic system has been developed by Griffith and co-workers. [74][75][76][77] This microfluidic model includes key features such as adjustable flow rates based on oxygen consumption and long-term steady maintenance of the oxygen gradient. This comprehensive system, using co-cultures of diverse heterogeneous cells, forms liver …”
Section: Liver On a Chipmentioning
confidence: 99%
“…[53] In these multicellular aggregates, the need for supporting gels or matrices is eliminated, the adverse effects 3D culture approach for generating a laminated cerebral cortex like structure from pluripotent stem cells. [57,58] Microfabrication Neuroprogenitor cells Microfluidic culture platform containing a relief pattern of soma and axonal compartments connected by microgrooves to direct, isolate, lesion, and biochemically analyze CNS axons [67,68] 3D bioprinting Primary human cortical neurons Discrete layers of primary neutrons in a RGD peptide-modified gellan gum [118][119][120] Intestine (Gut) Self-assembled Stem cells Identified intestinal stem cells and differentiated cells in vitro [59,60] Microfabrication Human epithelial cells Mimic contractility by using mechanochemical actuator [11,19,27,72] Liver Self-assembled Human stem cells 3D culture of self-renewing human liver tissue [61,62] Microfabrication Hepatocytes and fibroblasts Microengineered hepatic microtissues containing hepatocytes and fibroblasts [73][74][75][76][77] 3D bioprinting HepG2 and HUVEC Multilayered organ tissue model [96,[155][156][157] Vessel Microfabrication Rat brain endothelial cells 3D culture in microfluidic device [63][64][65][66] 3D bioprinting HUVECs and HUVSMCs Scaffold-less vessel formation using spheroid fusion [84][85][86][87][88][89][90][91]…”
Section: Engineering Technologiesmentioning
confidence: 99%